Diagnosis of Pemphigus associated with canine Leishmaniosis: a Case Report - Marques, Marilene da Silva; Arruda, Érico do Nascimento; Silva , Aline Maia (Brazilian Journal of Case Reports, 2021)
Pemphigus is an autoimmune dermatological condition that affects dogs and has in its clinical aspects a similarity to leishmaniasis, in which a differential diagnosis by means of histopathological examination is necessary. The present study sought to report a case of a dog, male, mixed breed, 10 years old, diagnosed with pemphigus and, later, diagnosed with leishmaniosis. Upon diagnosis, the animal presented only a lesion in the nasal plane, without apathy and without systemic changes, as evidenced by hematological and biochemical tests. After performing histopathological examination, the animal was diagnosed with pemphigus and underwent immunosuppressive treatment, obtaining significant improvement of the lesion. Under clinical suspicion of leishmaniasis, the animal was subjected to serological exams RIFI and ELISA resulting in an indeterminate result in ELISA and 1/40 reagent in the RIFI. As this is not a very relevant result, it was decided to perform another histopathological examination of the lesion where the presence of Leishmania spp. In this new exam it was not possible to obtain a diagnosis of pemphigus again, since the animal was under immunosuppressive treatment. Therefore, it is concluded that, in cases of co-infection of autoimmune diseases, such as pemphigus and canine leishmaniasis, the differential diagnosis by means of histopathological examination is extremely relevant to the patient’s therapeutic success and prognosis. Thus, it is necessary to note that the diagnosis of pemphigus does not exclude the diagnosis of leishmaniosis.